QoS boundary analysis of congestion control protocol based on stochastic network calculus in CRSN - Zhengjiang SONG; Xiaochen LI; Jiang CHEN (Dianxin kexue)
In order to guarantee the quality of service（QoS）of the cognitive radio sensor network（CRSN），the performance boundary of protocol used in CRSN is required to be accurately calculated. Therefore，a new QoS performance boundary analysis method based on stochastic network calculus （SNC）was proposed. The additive increase and multiplicative decrease（AIMD）congestion control mechanism in CRSN was used as evaluation object，and the communication delay and data backlog were used as QoS performance index. According to the sending rate distribution of the CR source sensor，the delay and backlog boundary were modeled based on stochastic network calculus with moment generating function. The experimental results show that calculated values of the model in different CRSN scenarios are within the theoretical bounds，which proves that the model has good performance.